Cancer treatment-related cardiac dysfunction in breast cancer survivors: A retrospective descriptive study using electronic health records from a Korean tertiary hospital. (August 2022) - Lim, Arum; Jang, Hyoeun; Jeon, Misun; Fadol, Anecita P.; Kim, Sanghee
Abstract: Purpose: The population overlap of breast cancer and cardiovascular diseases (CVDs) has increased due to early breast cancer detection and treatment and aging population trends. Moreover, breast cancer patients are at an increased risk for CVDs consequent to cancer treatments. We aimed to understand the characteristics of breast cancer patients with pre-existing CVDs and of those diagnosed with CVDs after receiving chemotherapy, and cancer treatment-related cardiac dysfunction's occurrence among Korean breast cancer patients with CVDs. Methods: This retrospective descriptive study, which collected clinical data from electronic health records from a Korean tertiary hospital, included 1200 female breast cancer patients with CVDs, aged 15–75 years. Results: A total of 45.7% had pre-existing CVDs, and 91.6% were classified as very high-risk for cardiotoxicity in the pre-existing CVDs group. Among the 1200 breast cancer patients with CVDs, only 439 patients had left ventricular ejection fraction (LVEF) data during their cancer treatment, and 121 received baseline assessment for LVEF. Of the 439 patients with LVEF data, 134 patients have been classified into cancer treatment-related cardiac dysfunction (CTRCD), and the median period from cancer diagnosis to CTRCD occurrence was 26.5 months. Conclusion: Despite the high cardiotoxicity risk of breast cancer patients with pre-existing CVDs, baseline studies of the risk assessment before chemotherapy were insufficient to support the prevention and early detection of cardiotoxicity. Therefore, it is paramount to consider how nurses focus on risk stratification before chemotherapy and support the regular monitoring of breast cancer survivors' cardiac functioning, to maintain optimal health status. Highlights: Breast cancer patients receiving chemotherapy are often not provided initial and regular cardiac function monitoring. Breast cancer patients with pre-existing cardiovascular diseases had a higher cardiotoxicity risk when starting chemotherapy. Both oncology and cardiology nurses should focus on the prevention of cardiovascular complications during chemotherapy.